Prophetic Conflicts in Jeremiah, Ezekiel, and Micah How Post-Exilic Ideologies Created the False (and the True) Prophets - Arena, Francesco (Mohr Siebeck, 2020)
Prophetische Konflikte in Jeremia, Hesekiel und Micha. Wie post-exilische Ideologien die falschen (und die wahren) Propheten schuf.
PublicationDate: 20200805
Keywords: Intertextuality -- Prophetic Literature -- Redaction Criticism -- Säkularität -- Comparative -- Biblical Prophecy -- Altes Testament -- Antike -- Array